Changing climate and glacio‐hydrology in Indian Himalayan Region: a review. (15th March 2016) - Singh, Shaktiman; Kumar, Rajesh; Bhardwaj, Anshuman; Sam, Lydia; Shekhar, Mayank; Singh, Atar; Kumar, Ramesh; Gupta, Akhilesh
Abstract : This study presents a comprehensive review of the published literature on the evidences of a changing climate in the Indian Himalayan Region (IHR) and its impacts on the glacio‐hydrology of the region. The IHR serves as an important source of fresh water for the densely populated areas downstream. It is evident from the available studies that temperature is significantly increasing in all parts of the IHR, whereas precipitation is not indicative of any particular spatiotemporal trend. Glacio‐hydrological proxies for changing climate, such as, terminus and areal changes of the glaciers, glacier mass balance, and streamflow in downstream areas, highlight changes more evidently in recent decades. On an average, studies have predicted an increase in temperature and precipitation in the region, along with increase in streamflow of major rivers. Such trends are already apparent in some sub‐basins of the western IHR. The region is particularly vulnerable to changing climate as it is highly dependent on snow and glacier melt run‐off to meet its freshwater demands. We present a systematic review of key papers dealing with changing temperature, precipitation, glaciers, and streamflow in the IHR. We discuss these interdisciplinary themes in relation to each other, in order to establish the present and future impacts of climatic, glaciological, and hydrological changes in the region. WIREs Clim Change 2016, 7:393–410. doi: 10.1002/wcc.393 This article is categorized under: Paleoclimates and Current Trends > Modern Climate Change